Exposure to cigarette smoke extract and lipopolysaccharide modifies cytoskeleton organization in bronchial epithelial cells. (26th November 2017) - D'Anna, Claudia; Cigna, Diego; Di Sano, Caterina; Di Vincenzo, Serena; Dino, Paola; Ferraro, Maria; Bini, Luca; Bianchi, Laura; Di Gaudio, Francesca; Gjomarkaj, Mark; Pace, Elisabetta
ABSTRACT: The integrity of the respiratory epithelium is crucial for airway homeostasis. Tobacco smoke exposure and recurrent infections of the airways play a crucial role in the progression and in the decline of the respiratory function in chronic obstructive pulmonary disease (COPD). The aim of this study was to detect differentially expressed proteins in a bronchial epithelial cell line (16-HBE) stimulated with cigarette smoke extract (CSE) and lipopolysaccharide (LPS), a constituent of gram-negative bacteria, alone and/or in combination, by using two-dimensional electrophoresis (2DE) analysis coupled with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Western blot analysis was applied to confirm the expression of significantly modulated proteins. Flow cytometry and immunofluorescence were used to assess F-actin polimerization by phalloidin method. Fourteen proteins, with significant (p < 0.05) changes in intensity, were identified at various experimental points: 6 were up-regulated and 8 were down-regulated. As expected, bioinformatic analysis revealed that most of these proteins are involved in anti-oxidant and immune responses and in cytoskeleton stability. Western blot analysis confirmed that: Proteasome activator complex subunit 2 (PSME2), Peroxiredoxin-6 (PRDX6), Annexin A5 (ANXA5) and Heat shock protein beta-1 (HSPB1) were reduced and Coactosin-like protein (COTL-1) was increased by co-exposure of CSE and LPS. Furthermore, LPS and CSE increased actin polimerization. In conclusion, although further validation studies are needed, our findings suggest that, CSE and LPS could contribute to the progressive deterioration of lung function, altering the expression of proteins involved in metabolic processes and cytoskeleton rearrangement in bronchial epithelial cells.